2017
DOI: 10.1007/s00415-017-8479-y
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar theta burst stimulation does not improve freezing of gait in patients with Parkinson’s disease

Abstract: Freezing of gait (FOG) in Parkinson’s disease (PD) likely results from dysfunction within a complex neural gait circuitry involving multiple brain regions. Herein, cerebellar activity is increased in patients compared to healthy subjects. This cerebellar involvement has been proposed to be compensatory. We hypothesized that patients with FOG would have a reduced ability to recruit the cerebellum to compensate for dysfunction in other brain areas. In this study cerebellar activity was modified unilaterally by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…In order to avoid studies with lower statistical power, 15 studies reporting samples with <10 patients were excluded. The therapies evaluated in those studies included visual cueing (laser light, staircase climbing) auditory cueing, tactile cueing, cueing exercise program, cognitive training, physical training, rTMS, and tDCS . All these approaches have been covered as well in the articles included in our review.…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid studies with lower statistical power, 15 studies reporting samples with <10 patients were excluded. The therapies evaluated in those studies included visual cueing (laser light, staircase climbing) auditory cueing, tactile cueing, cueing exercise program, cognitive training, physical training, rTMS, and tDCS . All these approaches have been covered as well in the articles included in our review.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies tested the effects of TBS on other PD symptoms, such as FOG. However, neither single session of iTBS applied to the left PM nor to the cerebellar hemisphere ipsilateral to the more affected limb improved FOG . Therefore, the clinical effects of TBS on PD remained inconclusive due to the small number of high‐quality studies.…”
Section: Noninvasive Brain Stimulation In Pdmentioning
confidence: 99%
“…One study also reported an improvement of the TUG test after rTMS of the dorsolateral prefrontal cortex [105] and another showed that gait variability and FOG occurrence were decreased after high frequency rTMS over the medial prefrontal cortex [37]. In contrast, neither cerebellum [80], nor premotor cortex stimulation [207] have a positive influence on FOG in PD. Contrasting results have been obtained for the supplementary motor area: whereas a benefit of rTMS for anticipatory postural adjustments duration [77] and FOG [98] were shown; one study did not report significant effects compared with sham stimulation [105].…”
Section: Electroencephalographymentioning
confidence: 99%